Thermoregulatory central venous catheter-associated thrombus – echocardiographic detection and novel approach to management. (February 2015) - Gillon, Stuart; Ammar, Thoraya; Adlam, Michael; Pahl, Clemens
An extensive caval thrombus was incidentally detected in a neurosurgical patient by clinician-delivered critical care echocardiography. Recent intracranial haemorrhage prevented therapeutic anticoagulation; the very proximal nature of the thrombus precluded standard deployment of an inferior vena cava filter. We describe the novel radiological technique employed to manage the thrombus, and examine whether a thermoregulatory central venous catheter inserted as part of standard neuro-critical care may have contributed to the risk and extent of the caval thrombus.